2014
DOI: 10.1111/j.1931-0846.2014.12039.x
|View full text |Cite
|
Sign up to set email alerts
|

Urban Heat and Climate Justice: A Landscape of Thermal Inequity in Pinellas County, Florida

Abstract: ABSTRACT. The combined effects of two global trends, urbanization and climate change, have generated considerable concern regarding their adverse and disproportionate impacts on the health of urban populations. This study contributes to climate-justice research by determining whether elevated levels of urban heat, indicated by land surface temperature (LST), are distributed inequitably with respect to race/ethnicity, age, and socioeconomic status in Pinellas County, Florida. Our study utilizes 2010 MODIS and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 51 publications
5
32
0
Order By: Relevance
“…For the reduction of spatial autocorrelation and better model performance, the SAM was employed, and the SEM was identified as the most suitable model, based on an LM diagnostic test. The results of this study are in line with earlier studies in other fields [15][16][17], and confirm that the SAM can be used to identify statistically significant relationships among variables, using the spatially autocorrelated model residuals. Through a spatial error model, this study showed that vulnerable people (less-educated people, minorities) and places (high precipitation, fewer manufacturers, fewer open spaces, lower densities, and high slope) are more likely to experience disaster damage.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For the reduction of spatial autocorrelation and better model performance, the SAM was employed, and the SEM was identified as the most suitable model, based on an LM diagnostic test. The results of this study are in line with earlier studies in other fields [15][16][17], and confirm that the SAM can be used to identify statistically significant relationships among variables, using the spatially autocorrelated model residuals. Through a spatial error model, this study showed that vulnerable people (less-educated people, minorities) and places (high precipitation, fewer manufacturers, fewer open spaces, lower densities, and high slope) are more likely to experience disaster damage.…”
Section: Discussionsupporting
confidence: 91%
“…A geographically weighted regression (GWR) was applied to find the spatially-varying relationship between water quality and land use, showing the decrease of spatial autocorrelation in the model residuals [11]. A spatial autoregressive model (SAM) has been used in disaster-related studies, including environmental justice, flood mitigation, and social vulnerability, to account for the spatial autocorrelation in the model residuals or independent variables [14,15,17,40]. Myers et al identified the relationship between social vulnerability and migration measures using a spatial lag model (SLM) after two hurricanes-Katrina and Rita [40].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This research sought to determine whether thermal inequity might exist in an Australian suburb, extending environmental justice research from North America Chakraborty 2014, Mitchell andChakraborty 2015) based primarily upon higher density and inner-city locales (Jesdale et al 2013). We tested statistical associations between indicators of social disadvantage and measures of climate change awareness, concern and perceived efficacy in adapting to impacts, as well as residents' energy expenditure, perceived thermal comfort, and disposition towards use of green infrastructure as a policy intervention to lessen heat in built environments.…”
Section: Discussion and Concluding Commentsmentioning
confidence: 99%
“…This urban heat island (UHI) effect results in substantially higher temperatures in the urban core than in suburbs and hinterlands (Harlan et al 2007, Mccarthy et al 2010, Maller and Strengers 2011, Xiang et al 2014. As a result of uneven social geographies, urban heating disproportionately impacts lowerincome and ethno-racially marginalised populations -a phenomenon termed 'thermal inequity' Chakraborty 2014, Mitchell andChakraborty 2015). Such populations can become spatially concentrated in hotter urban environments (Harlan et al 2007), and may not be able to afford to cool their homes due to lower-incomes, an energy security concern (Byrne and Portanger 2014).…”
Section: Introductionmentioning
confidence: 99%